Pisces, Siluriformes, Ictaluridae, Ictalurus punctatus (Rafinesque, 1818): First record in middle Paranapanema river reservoir, aquaculture and exotic species dispersion - Zanatta, Augusto Seawright [UNESP]; Ramos, Igor Paiva [UNESP]; da Silva, Reinaldo José [UNESP]; Langeani, Francisco [UNESP]; Carvalho, Edmir Daniel [UNESP] (Pensoft Publishers, 2010)
This is the first report of Ictalurus punctatus in the middle Paranapanema river basin; the occurrence of this species may be associated with the expansion of pisciculture in cage farms in the Brazilian territory as a whole. © 2010 Check List and Authors.